2010
DOI: 10.3855/jidc.819
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bacterial and parasitic infections and cancer: a review

Abstract: Background: A relatively underestimated facet of infectious diseases is the association of chronic bacterial and parasitic infections with cancer development. Therefore, we sought to evaluate the evidence regarding the association of such infections with the development of malignancy, excluding the overwhelming evidence of the association of Helicobacter pylori and cancer. Methodology: We searched Pubmed, Cochrane, and Scopus without time limits for relevant articles. Results: There is evidence that some bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 142 publications
2
65
1
1
Order By: Relevance
“…Currently, approximately a quarter of the worldwide malignancies are attributed to microbial contribution [18] and orodigestive cancers are among the top five leading causes of cancer mortalities [16]. One of the particularly devastating examples of orodigestive cancer mortality with escalating prevalence is oral squamous cell carcinoma (OSCC), which claims an estimated 7500 lives yearly in the United States [19].…”
Section: Cancer and Oral Microbesmentioning
confidence: 99%
“…Currently, approximately a quarter of the worldwide malignancies are attributed to microbial contribution [18] and orodigestive cancers are among the top five leading causes of cancer mortalities [16]. One of the particularly devastating examples of orodigestive cancer mortality with escalating prevalence is oral squamous cell carcinoma (OSCC), which claims an estimated 7500 lives yearly in the United States [19].…”
Section: Cancer and Oral Microbesmentioning
confidence: 99%
“…The incidence of and mortality associated with CC are increasing worldwide and an etiological study found that the daily ingestion of germs, including Helicobacter spp., and parasites might contribute to the development of CC (Samaras, et al 2010). Liossi et al found 17β-estradiol (E2), but not testosterone, immunoactivity in CC lesions (Liossi, et al 1988), suggesting potential protective/redundant roles of male hormones in CC progression (Liossi et al 1988).…”
Section: Part II Androgen/ar Signaling In Liver Cancermentioning
confidence: 99%
“…Nevertheless, contribution of bacterial infection to cancer development has been suggested based on various epidemiological studies (Mager, 2006;Samaras et al, 2010). Most accepted is the link between Helicobacter pylori and gastric cancer (Polk and Peek, 2010).…”
Section: Introductionmentioning
confidence: 99%